Modeling of Combined Impact and Blast Loading on Reinforced Concrete Slabs - P. Del Linz; S.C. Fan; C.K. Lee (Latin American Journal of Solids and Structures)
Abstract Explosive devices represent a significant threat to military and civilian structures. Specific design procedures have to be followed to account for this and ensure buildings will have the capacity to resist the imposed pressures. Shrapnel can also be produced during explosions and the resulting impacts can weaken the structure, reducing its capacity to resist the blast pressure wave and potentially causing failures to occur. Experiments were performed by the Defence Science and Technology Agency (DSTA) of Singapore to study this combined loading phenomenon. Slabs were placed on the ground and loaded with approximately 9 kg TNT charges at a standoff distance of 2.1 m. Spherical steel ball bearings were used to reproduce the shrapnel loading. Loading and damage characteristics were recorded from the experiments. A finite element analysis (FEA) model was then created which could simulate the effect of combined shrapnel impacts and blast pressure waves in reinforced concrete slabs, so that its results could be compared to experimental data from the blast tests. Quarter models of the experimental concrete slabs were built using LS-Dyna. Material models available in the software were employed to represent all the main components, taking into account projectile deformations. The penetration depth and damage areas measured were then compared to the experimental data and an analytical solution to validate the models.